Diaspora externalities - Hillel Rapoport (IZA Journal of Development and Migration, 2019)
This review article surveys the recent economic literature on diaspora networks, globalization, and development. Diasporas are shown to contribute to the economic and cultural integration of source (i.e., developing) countries into the global economy. I first review the effect of diaspora networks on core globalization outcomes such as trade, foreign investments, and the diffusion of knowledge and technology across borders. I then turn to the cultural and political sway of the diaspora, investigating the impact of emigration on the formation of political attitudes, fertility behavior, and other aspects of culture in the home country.
Keywords: F21; F22; F63; J61; O11; O15; 330; diasporas; globalization; international migration; development; brain drain; trade; FDI; knowledge diffusion; social remittances; cultural convergence